2015
DOI: 10.1159/000430096
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of School-Based Oral Health Program on Oral Health Knowledge and Practices and Oral Health-Related Quality of Life

Abstract: Objective: To evaluate the effects of exposure to the School Oral Health Program (SOHP) during primary school years on the current oral health (OH) knowledge and practices and OH-related quality of life (OHRQoL) of Kuwait University students. Subjects and Methods: 300 university students, aged 17.6-24.3 years, completed avalidated questionnaire that consisted of 5 sections about demographics, health self-evaluation, OH knowledge and practices and OHRQoL. Of these students, 260 were female, 40 male, 262 single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Alsumait et al reported that the case group in the School Oral Health Program (SOHP), were twice more aware of the relationship between gum problems and heart diseases than non‐SOHP (OR = 2.95% CI: 1.15, 3.48, P = .013). The probability to be affected by dental health issues among the control group subjects was 2 times higher than the case group (OR = 2.28, 95% CI: 1.41, 3.68, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Alsumait et al reported that the case group in the School Oral Health Program (SOHP), were twice more aware of the relationship between gum problems and heart diseases than non‐SOHP (OR = 2.95% CI: 1.15, 3.48, P = .013). The probability to be affected by dental health issues among the control group subjects was 2 times higher than the case group (OR = 2.28, 95% CI: 1.41, 3.68, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…A further task resulting from this initial consultation is the subsequent treatment that often requires interdisciplinary collaboration with other disciplines of dentistry [5]. Furthermore, it seems to be important that not just dentists, but also medical doctors should be taught in oral health education [26] and public health systems should implicate oral health programmes [27] in order to improve oral health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Administered tooth brushing, oral health education/promotion, fluoride and fissure sealant application, and/or different treatments are activities included in school programs [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…These activities can constitute children's health-related convictions, demeanor, behaviors, and values. Also, prove proposes that a healthy life of adulthood can be impacted by oral health administrations [3], [4]. Even though school-based oral health instructions are viable in enhance oral health information and advancing oral hygiene and practices [5], [6], there could be an inquire about crevice within the writing on the effect of multiapproach preventive programs [1].…”
Section: Introductionmentioning
confidence: 99%